Exploring the association between gene sequence polymorphisms within the angiogenesis and extracellular matrix regulatory pathways and shoulder pain and disability following breast cancer treatment - Mafu, Trevor (Department of Human Biology, 2025)
Shoulder pain and disability are common sequelae of breast cancer treatment in women, with an understated negative impact on the quality of life of affected individuals and a poorly characterised aetiology. A better understanding of the aetiology of shoulder pain and disability in breast cancer survivors is urgent to develop and/or integrate effective treatments to mitigate the related reduction in quality of life– this is especially important given the increasing cancer survivorship in societies such as in South Africa where a high percentage of households are female-headed and a resource-based public healthcare system is used by the majority. Previous studies have explored treatment-related and patient-related factors that modulate risk of upper-limb impairments in breast cancer survivors, including shoulder pain and disability. However, there is a paucity of relevant studies on key genetic factors. Genetic factors within angiogenesis-related signalling and extracellular matrix (ECM) regulating pathways have been implicated in non-cancer-related studies of soft tissue conditions of the shoulder that are associated with pain and display movement dysfunction similar to that seen in breast cancer post-treatment shoulder morbidity. It is largely unknown whether or not key factors within the angiogenesis-related and ECM-regulating signalling pathways may modulate risk of shoulder pain and disability in breast cancer survivors.